Fighting for political freedom : comparative studies of the legal complex and political liberalism - Halliday, Terence C. (Terence Charles); Karpik, Lucien; Feeley, Malcolm M. (Oñati international series in law and society., 2007)
On the basis of some 16 case studies from across the world, this book presents a theoretical link between lawyers and political liberalism having wide-ranging application over radically diverse situations in Asia and the Middle East, North and South America, and Europe.